PENGEMBANGAN KAWASAN WISATA RESORT AKAR BERAYUN LEMBAH HARAU OLEH DINAS KEBUDAYAAN PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN LIMAPULUH KOTA SUMATERA BARAT - Annisa Rahmi; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Tourism development one of the impact of Teritory Authonomy implementation since occured from January 1, 2001. Tourism is teritory potency that should be explore to increase the economic prosperity of society. The Construction and tourist development Lembah Harau did not experience significant changes and only whitin a certain time, so that facilities and public property looked like a poorly maintained. The problem from this research is how the development resort area of Akar Berayun Lembah Harau at Limapuluh Kota at West Sumatra and the factors that can be a barrier. This research aims to describe the development and inhibiting factors implementation tourism development of Resort Area Akar Berayun Lembah Harau by Department of Tourism Culture Youth and Sports regency of lima puluh kota at west Sumatera .This research applying qualitative methods and with techniques data collection and interview, documentation, and observation. The author use managment theories by Richard George R. Terry and this theories consists of the actions of planning, organizing, and controlling to determine and achieve objectives through the utilization of human resources and other resources. The sources of this research are from of interview, observation, and documentation.The implementation tourism development of Resort Area Akar Berayun Lembah Harau by Department of Tourism Culture Youth and Sports regency of lima puluh kota at west Sumatera has not been realized with good. Because inhibiting factors implementation tourism development of Resort Area limited, by natural factor and the lack of people participation. departement and tourism in order to compete with other regions, goverment will be not progress without the good planning. implementation in accordance with predefined and monitoring and reporting for the evaluation work program. For the Department must improve coaching, improve good cooperation and sustainable joint with working partners with govermant as well as the non govermental organizationsand partners other public authorities or private, the community must play an active to support the development of tourism because people are the main perpetrators of the tourism.Keywords: Akar Berayun , Development, Lembah Harau, Resort Area